Islamic Republic of Iran : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation highlights that during the first four years of the Third Five-Year Development Plan (2000/01-2003/04), Iran's real GDP grew by 5.6 percent on average. The external current account was in surplus, external debt was reduced to a very low level, international reserves increased, and the unemployment rate declined. Real GDP grew by 6.7 percent in 2003/04, with strong contribution from both the oil and non-oil sectors. The unemployment rate declined to 11.2 percent from 14.1 percent in 2000/01.